Industrial Ecology-Design of Closed Loop System to Minimize Waste and Reduce Environmental Impact (International Journal of Innovative Research in Engineering & Management, 2023)
Industrial ecology is a concept that aims to  design industrial systems in a manner that mimics natural  ecosystems, minimizing waste generation and reducing  environmental impact. This abstract provides an overview  of the principles and strategies involved in the design of  closed-loop systems within industrial ecology. In recent years, the negative impact of industrial processes  on the environment has become a growing concern.  Traditional linear production systems, characterized by a  "take-make-dispose" approach, have resulted in significant  waste generation and environmental degradation. To  address this issue, the concept of a closed-loop system has  gained prominence. A closed-loop system aims to minimize  waste and reduce environmental impact by designing  processes that maximize resource efficiency, recycle  materials, and minimize the release of harmful substances.  This research focuses on the design of a closed-loop system  that incorporates principles of circular economy and  sustainable manufacturing practices. The proposed system  emphasizes the integration of various components,  including material selection, product design, manufacturing  processes, and end-of-life management. The primary  objective is to develop a comprehensive framework that  enables the transformation of linear production systems into  circular systems, ensuring the efficient use of resources  throughout the product life cycle. The methodology for  designing the closed-loop system involves several steps.  Firstly, a detailed analysis of the existing production  processes and waste generation patterns is conducted to  identify areas for improvement. Next, strategies for waste  reduction and resource optimization are explored, such as  the adoption of eco-design principles, implementation of  recycling and reprocessing techniques, and establishment of  reverse logistics systems.
Keywords: Closed Loop; Waste Management; Recycle; Re-Use; Plastic; Environment; LCA